The gut-brain axis mediates precocious puberty induced by environmentally relevant low-dose endocrine-disrupting chemical mixtures - Wu, Hui; Wei, Guo; Huang, Shuo; Wan, Lingyu; Xu, Qin; Huang, Congfu (Frontiers in Endocrinology, 2026)
BackgroundThe global rise in precocious puberty (PP) is increasingly linked to exposure to endocrine-disrupting chemicals (EDCs). However, the mechanisms by which environmentally relevant, low-dose mixtures of EDCs influence PP remain inadequately explained by direct endocrine disruption.ObjectiveThis systematic review evaluates a novel hypothesis: that disruption of the gut-brain axis (GBA) serves as a pivotal mechanism in EDC mixture-induced PP.MethodsWe synthesized evidence from 87 studies (45 human, 32 animal, 10 in vitro) following PRISMA 2020 guidelines. An exploratory Random Forest analysis was employed to identify key mediators and estimate the relative contribution of the GBA pathway.ResultsPerinatal exposure to low-dose EDC mixtures consistently induced gut dysbiosis, characterized by reduced microbial diversity (Shannon Δ = −1.8), a 40% decrease in Lactobacillus, and a 1.5-fold increase in Bacteroides. This dysbiosis was linked to impaired production of butyrate (↓50%) and secondary bile acids, increased intestinal permeability (FITC-dextran ↑80%), and systemic inflammation (IL-6 ↑1.8-fold). Fecal microbiota transplantation from PP donors into germ-free mice recapitulated early pubertal onset, supporting a causal role for gut microbiota. Exploratory modeling suggested that mediators within the GBA pathway could be associated with a large share (approximately 68%) of the model-internal variance explanation for PP risk at low experimental doses (≤1 μg/kg/day), indicating its potential prominence over direct endocrine disruption in this analysis. Significant synergistic effects (Synergy Index > 2.3) were observed under mixture exposures.ConclusionThis review identifies the GBA as a critical and previously underappreciated mechanism for low-dose EDC mixture-induced precocious puberty in a dose-dependent manner. Our findings underscore the need for regulatory paradigms and future research to integrate this pathway when assessing the risks of complex, real-world chemical mixtures.